Pengaruh padat tebar berbeda terhadap pertumbuhan, kelangsungan hidup, dan efisiensi pakan juvenil udang vaname (Litopenaeus vannamei) - Gotama, Kadek Bayu Candra; Julyantoro, Pande Gde Sasmita; Wijayanti, Ni Putu Putri (Current Trends in Aquatic Science; Vol 7 No 1 (2024), 2024)
Vaname shrimp ( Litopenaeus vannamei ) has advantages, such as being more responsive to feed, resistant to diseases and poor environmental conditions, fast growth, high survival rate, and high stocking density. This study aims to examine the effects of different stocking densities on the growth, survival rate, and feed efficiency of vaname shrimp. Vaname shrimp (±0.6 g/shrimp). were stocked in fiber tanks with a volume of 500 liters and filled with seawater with a salinity of 35 ppt. This study used an experimental method with 3 different stocking density treatments: 200 individual/m 3 (A), 400 individual/m 3 (B), and 600 individual/m 3 (C), repeated three times per treatment. The shrimps were cultivated for 60 days and fed at a rate of 5% of their body weight/day four times a day. The results showed that average growth shrimp in treatment A, B, and C were 12.10 g, 10.14 g, and 7.37 g, respectively. The survival rate of shrimp in the treatmen A. B, and C were: 72%, 46,3%, and 56%, respectively. The FCR in the treatment A, B, and C were 0.95; 1.4; and 1.26. One Way ANOVA statistical analysis indicated significant differences (P<0,05) between treatments A dan C in terms of mean body weight growth, as well as between treatments A and B in terms of FCR. This study indicated that different stocking densities affect the growth, survival rates, feed efficiency, and water quality of vaname shrimp.